Accuracy of ALMA estimates of young disk radii and masses: predicted observations from numerical simulations - Tung, Ngo-Duy; Testi, Leonardo; Lebreuilly, Ugo; Hennebelle, Patrick; Maury, Anaëlle; Klessen, Ralf S.; Cacciapuoti, Luca; González, Matthias; Rosotti, Giovanni Pietro; Molinari, Sergio (Astronomy and astrophysics, 2024)
Protoplanetary disks, which are the natural consequence of the gravitational collapse of the dense molecular cloud cores, host the formation of the known planetary systems in our universe. Substantial efforts have been dedicated to investigating the properties of these disks in the more mature Class II stage, either via numerical simulations of disk evolution from a limited range of initial conditions or observations of their dust continuum and line emission from specific molecular tracers. The results coming from these two standpoints have been used to draw comparisons. However, few studies have investigated the main limitations at work when measuring the embedded Class 0/I disk properties from observations, especially in a statistical fashion.